Effect of pretreatments on cellulosic composition and morphology of pine needle for possible utilization as substrate for anaerobic digestion. (October 2020) - Mahajan, Rishi; Chandel, Shalini; Puniya, Anil Kumar; Goel, Gunjan
Abstract: Waste residues from agricultural and forest resources have received much attention as potential source of lignocellulosic biomass (LCB) especially after the "food-versus-fuel" conflict. Therefore, exploring the potential of LCB (especially forest biomass) as a resource for sustainable bioenergy generation is highly promising. The present study reports the structural modification in the cross-linking of lignocellulosic complex in pine needle forest biomass after pretreatments: milling, steam explosion and acid-base-acid treatments. The changes in morphology and composition of the cellulose and lignin in pine needles after pretreatments was evaluated using Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared (FT-IR) microspectroscopy, Energy Dispersive Spectroscopy (EDS) and Scanning Electron Microscopy (SEM). Field Emission Scanning Electron micrographs revealed that pretreatments resulted in changes in orderly arrangement of interwoven fibrils, surface abnormalities in cells surrounding stomatal opening and exposure of vascular bundle. FT-IR of pretreated substrate indicated significant changes in functional moieties of ester bond between lignin and hemicelluloses, phenol hydroxyl moieties and aromatic ring associated with lignin and hydrogen bonding in cellulose. The findings in the present study thus open up avenues for exploring potential of pretreated pine needles for renewable bioenergy generation. Anaerobic digestion (AD) of the pretreated biomass resulted in 21.4% higher methane levels as compared to untreated pine litter. Appearance of lignin droplets and deposition of coalescent materials on pre-treated biomass surface was also observed in the present study. These colloidal lignin particles could serve as potential nanocomposites, for application in biomaterial applications. Highlights: Sequential physico-chemical pretreatment methodology for pine needle forest litter. Analytical techniques revealed ultrastructural and compositional modifications. Anaerobic digestion of pretreated pine needle for bioenergy generation. Sequential pretreatment has potential for biosynthesis of lignin nanocomposites.